Hubungan antara kualiti hidup dan status kesihatan mental ibu tunggal B40 di Malaysia - Siti Marziah Zakaria,; Wan Nurdiyana Wan Yusof,; Asila Nur Adlynd Mohd Shukry,; Noremy Md Akhir, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Single mothers are a vulnerable group in terms of social and economic conditions and are at risk of facing various mental and physical health problems. Single mothers with children are the poorest in Malaysia. Challenges such as financial problems, societal stigma as well as social and psychological problems are frequently reported among B40 single mothers. A quantitative study was conducted on 567 single mothers in Malaysia in 2021 to analyze the status of their quality of life and mental health during the COVID-19 pandemic. This article will determine the relationship between quality of life and mental health of B40 single mothers in Malaysia. The sample was selected by purposive sampling, by setting inclusive and exclusive criteria. The DASS-21 scale (Depression, Anxiety, and Stress Scale 21) and THE SPHERE Quality of Life Scale were used to test the constructs of mental health and quality of life. Correlation analysis shows that there is a significant negative relationship between quality of life and mental health (r = -0.265, p < 0.05) of B40 single mothers. This shows that the higher the respondent's quality of life score, the lower the mental health score. Single mothers who report high symptoms of depression, anxiety and stress generally have lower levels of quality of life. The results of this study will provide input to the planning of programs for the empowerment of B40 single mothers in Malaysia to further improve their quality of life.